Editorial Preface - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak (Idealogy Journal; Vol 3 No 1 (2018): Idealogy Journal (April 2018)DO - 10.24191/idealogy.v3i1.279, 2018)
Overview of the Idealogy of Arts and Social Science by the Chief and Deputy Chief Editor.